Refining the chronology and distribution of mid-fifteenth to mid-seventeenth century Indian Ocean world glass. (December 2021) - Craig, Jennifer
Abstract: Abstract : Morphological and compositional analysis of glass beads from three shipwrecks in the Indian Ocean world has increased our understanding of the chronology and distribution of mid-fifteenth to mid-seventeenth century glass.